Imago України та українців у журналістській та фікційній свідомості Джона Стейнбека - Ничко, О. (Питання літературознавства, 2009)
У центрі уваги – візії Стейнбека-журналіста та Стейнбека-письменника радянської Росії. Досліджується стейнбеківський гетеростереотип України та українця, простежуються прояви української психоментальності на матеріалах малознаних мандрівних нотаток американського письменника „A Russian Journal”(1948). The article is the continuation of a set of articles on John Steinbeck’s vision of the Soviet Russia as a journalist and as a writer. John Steinbeck’s heterostereotype of Ukraine and Ukrainians is investigated. Based on little known travel articles of the American writer “A Russian Journal”(1948) Ukrainian psychomentality is traced.